383 Urticaria and Arthralgias in a Nine-Year-Old with Recurrent Urinary Tract Infections - Butt, Ahmed (World Allergy Organization Journal, 2012)
BACKGROUND: Serum sickness is a type III immune complex hypersensitivity reaction occurring after exposure to foreign antigens, most commonly medications. Symptoms typically begin 1 to 3 weeks after initial exposure to the offending agent and include fever, malaise, urticarial or morbilliform rashes and arthralgias which may progress to arthritis, nephritis, neuropathy or vasculitis. We report a case of drug-induced serum sickness in a patient who had previously tolerated trimethoprim/sulfamethoxasole (TMP/SMX) for treatment of recurrent urinary tract infections. METHODS: A 9 year-old female presented with a pruritic, erythematous rash that began 2 days after completing a 10 day course of TMP/SMX for a urinary tract infection. TMP/SMX had previously been prescribed to treat recurrent urinary tract infections without adverse side effects. RESULTS: Initially she developed a fever and a blotchy rash with patches of erythema which started on the torso and progressed to generalized urticaria over a 24 hour period. Associated symptoms included fatigue, lethargy, generalized myalgias and arthralgias with swelling limited to the left knee, ankles and fingers. No mucosal lesions, nausea, vomiting or diarrhea were present. Pertinent findings on physical examination included mild edema of the left knee without associated erythema or warmth and proximal and distal interphalangeal joints of the hands, wrists, knees and ankles absent of an effusion, but tender to palpation with full range-of-motion. Urticarial lesions with serpiginious borders and central clearing were noted on the trunk and extremities including the palms but not soles. Hyperpigmented areas at sites of previous urticarial lesions were present. Prednisone, 10 mg 3 times daily, and cetirizine, 10 mg daily, was prescribed and within 24 to 48 hours, all symptoms improved. No further laboratory studies were obtained. Prednisone was tapered over a 2 week period and cetirizine was discontinued simultaneously without recurrence of symptoms. The patient was advised to avoid TMP/SMX indefinitely. CONCLUSIONS: Medications are the most common cause of serum sickness with TMP/SMX being frequently implicated. Immune complex reactions generally occur a few weeks after initial exposure to a medication; however, drug -induced serum sickness should still be considered in cases to which an agent may have been previously tolerated.